Isolation of cellulase producing bacteria from EFB compost, sawdust and rhinoceros beetle guts / Mohd Alif Haikal Ramly - Ramly, Mohd Alif Haikal (2019)
The microbial succession occurs due to the establishment of a new species that modified the environment. The decomposition of leaves and other organic materials produce rich top soil. Since plant made up from cellulose, this experiment purposely to isolate and identifies bacteria that able to decompose cellulose. The enzymes cellulases are which hydrolysis cellulosic biomass and are microorganisms that being produced by growing from cellulosic matters. Important enzyme cellulase which can be obtained from cheap agrowastes, as well as cellulose as substrates by using solid state fermentation and submerged fermentation. Cellulase enzyme can degrade cellulose protein and can be produced by cellulolytic bacteria and fungi, in this experiment only bacteria will be used. All of this because the bacteria have higher rate growth than fungi and also it has good potential to produce cellulase. Therefore, in this study it is really important to isolate and identify the cellulase producing bacteria.